Bibliometric analysis of monoclonal antibodies for atherosclerosis - Jiqing Ma; Kaiwen Zhao; Yalin Zhu; Wen Xu; Jie Huang; Xiaolong Wei; Zhiqing Zhao (Human Vaccines & Immunotherapeutics, 2023)
ABSTRACTAtherosclerosis (AS) is a prevalent cardiovascular disease that greatly increases mortality in the aging population and imposes a heavy burden on global healthcare systems. The purpose of this study is to examine the research structure and current trends of monoclonal antibodies (mAbs) against AS from a bibliometric perspective, since the development of these drugs is currently booming. This study collected articles and reviews on mAbs against AS from the Web of Science Core Collection, spanning from 2003 to 2022. Biblioshiny was utilized to analyze and visualize the characteristics of countries, regions, authors, institutions, and journals included in this collection. We used VOS viewer to illustrate the frequency of country co-occurrence, and CiteSpace to visualize co-cited reference, keywords co-occurrence, keywords citation bursts, keywords clustering and timeline plots. The study included 1325 publications, with the United States emerging as a leading contributor to the field. ATHEROSCLEROSIS, CIRCULATION and ARTERIOSCLEROSISTHROMBOSIS AND VASCULAR BIOLOGY are core journals that publish high-quality literature on the latest advances in the field. Noteworthy authors with numerous high-quality publications include Witztum JL and Tsimikas S. Currently, lipid metabolism and inflammation are the main research areas of interest in this field. The mAbs against AS is an evolving field, and ongoing research continues to advance our understanding. This paper provides a comprehensive overview of the current state of knowledge in this area, highlighting two primary research directions: inflammation and lipid metabolism. Additionally, the paper identifies emerging research hotspots, which will provide researchers with useful insights to guide future investigations and anticipate research directions.